Surgical behavior of patients with liver trauma. Calixto García General University Hospital, 2021-2013 - Roberto Lázaro Blanco Sosa; Eddison Mauricio Matute Gómez; Edmundo Héctor Balbuena Valencia (Medisur)
Foundation: The liver is the most affected organ in penetrating abdominal trauma, and is the second most harmed when it comes to closed trauma, a fact that bases the relevance of studies that describe and deepen the issue of surgical approach to patients with liver trauma. Objective: Describe the surgical behavior of patients with a diagnosis of liver trauma. Methods: Descriptive, transverse study, made in 25 patients diagnosed with liver trauma and required surgical treatment at the General Calixto García University Hospital, in Havana, from January 2021 to December 2023. Results: The ultrasound focused on trauma and computerized axial tomography were the most used diagnostic methods (68.0 %). The right lobe was the most frequent location (72.0 %), as well as the lesions of grade II (44.0 %) according to the organic lesion scale. The most used surgical treatment was the most electrocoagulation hepatorraph (64.0 %); and the most observed complication, the infection of the surgical wound (16.0 %). Most patients graduated alive. Conclusions: The surgical behavior of patients with a diagnosis of liver trauma was characterized by the prevalence of lesions in the right lobe and those treated with hepatorraph. As stated by the results, imaging studies and ultrasound focused on trauma constitute an effective tool for diagnosis.